(untitled) (Conference Zone, 2022)
In this article, bright aspects, including artistic interpretations, characteristic of moral appearance of ashik (lover) and, particularly, the topic of love in the works of the uzbek poet Alisher Navoi are mentioned . The lyrical hero of the great poet, some thoughts about the history and teaching of his love have been revealed